Synthesis of the proposed structure of sibiriaester B and evaluation of its immunomodulatory properties. (14th September 2021) - Sim, Myeonghyeon; Yoon, Jeong Min; Kim, Soobin; Kim, Kwangmi; Han, Young Taek
Abstract: Herein, we report a concise synthesis of the proposed structure of sibiriaester B, a novel antioxidant phenyl caffeate derivative isolated from the leaves of Armeniaca sibirica . Proposed sibiriaester B was obtained via simple esterification between the known TBS‐protected caffeic acid and the commercially available methyl 4‐hydroxybenzoate, and subsequent deprotection. However, the NMR spectral data of the synthesized sibiriaester B were not consistent with those in previous reports. The structure of the synthesized sibiriaester B was confirmed using combined 2D‐NMR analysis, including COSY, HSQC, and HMBC. The synthesized sibiriaester B was observed to exhibit more potent immunomodulatory activity in murine epidermal T cells than p ‐hydroxyphenyl caffeate, an immunomodulatory natural caffeate derivative, as treatment with sibiriaester B significantly reduced the production of interleukin 13 by murine epidermal T cells at lower concentrations than p ‐hydroxyphenyl caffeate. Abstract : Proposed structure of sibiriaester B (3 ), a novel antioxidant phenyl caffeate derivative isolated from the leaves of Armeniaca sibirica, was synthesized from the known TBS‐protected caffeic acid. Sibiriaester B (3 ) was found to exhibit more potent immunomodulatory activity in murine epidermal T cells than p ‐hydroxyphenyl caffeate (2 ), an immunomodulatory natural caffeate derivative, as treatment with 3 significantly reduced the production of interleukin 13 by murine epidermal T cells at lower concentrations than 2 .